The construction and purification of truncated N terminal and C terminal versions of LeuI, the Immunity gene of Leucocin A, from Leuconostoc gelidum 187-22 - Tambe, Azraa (Stellenbosch : Stellenbosch University, 2025)
Thesis (MSc)--Stellenbosch University, 2025.